IMPLEMENTASI MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN SIMPLE PRESENT TENSE - Djoko Sri Bimo; Maria Yustina Rensi Dartani; Binti Muflikah (Universitas Terbuka, 2022)
Multimedia is a new concept and technology in the field of information technology where text, images, sound, animation, and video are combined on a computer to be stored, processed, and presented both linearly and interactively. This study aims to describe the implementation of interactive multimedia and to describe the success rate of class VIII in learning the Simple Present Tense. This study used a quantitative research approach, with a quasi-experimental type, and a randomized pretest-posttest comparison group design. The sample was class VIII-PK 1 as the experimental group 1, class VIII-PK 2 as the experimental group 2, using cluster random sampling technique. With this interactive multimedia learning method, it was hoped that the students’ ability in mastering English grammar could increase.